Country Risk Ratings of Small Island Tourism Economies - Riaz Shareef (Fondazione Eni Enrico Mattei (FEEM), 2004)
Over the last twenty years, there has been a growing fascination within public and academic circles about the livelihood of islands with small populations and territory which are present in each of the world's great oceans. The Small Island Tourism Economies analysed in this paper vary profoundly in their size, land area, and location. Moreover, they have depended heavily on financial aid from their former colonists for infrastructure development, which has declined dramatically since the collapse of Communism. These economies also differ in their narrow natural resource bases on land and in water, in their prospects for self reliance in economic development, and their overwhelming reliance on tourism as a source of exports. These economies are developing countries which need a consistent inflow of foreign direct investment to maintain economic growth. Such sovereign island economies differ in the extent to which they are home to a multitude of ethnic diversity, political systems, historical experience, economic and environmental vulnerability, ecological fragility, the types of risks facing private investors, and in the extent to which they are perceived as, or perceive themselves to be, insular and peripheral. In spite of the vast diversity as well as similarities, researchers are fascinated by the world of small island economies, and are intrigued by their unique features which cannot be addressed through a generalised set of rules. This paper analyses the geographical, historical, economic, tourism-oriented and institutional characteristics, as well as vulnerability to changes in the international economic, financial and political climates, of twenty Small Island Tourism Economies. The snapshot images provide a comparative assessment of the international country risk ratings, and highlight the importance of economic, financial and political risk ratings as components of a composite risk rating for Small Island Tourism Economies.
Keywords: F00; R14; 330; Small size; Tourism; Volatility; Vulnerability; Country risk ratings; Economic risk; Financial risk; Political risk; Composite risk; Länderrisiko; Insel; Tourismuswirtschaft; Welt